Tracking Control Of Vertical Pneumatic Artificial Muscle System Using Pid - Ming Hui, Tan; Shin Horng, Chong; Teng Fong, Tan; Ahmad Zaki, Shukor; Sakthivelu, Vasanthan; T.C., Ma; Mohamad Riduwan, Md Nawawi (Penerbit Universiti, UTeM, 2016)
The advantages of pneumatic system such as compactness, high power to weight ratio, ease of maintenance, cleanliness and inherent safety led to the development of McKibben muscle and pneumatic artificial muscle (PAM). However, the air compressibility and the lack of damping ability of PAM bring dynamic delay to the pressure response and causes oscillatory motion to occur. It is not easy to realize the motion with high accuracy and high speed due to all the non-linear characteristics of pneumatic system. In this paper, we present a vertical PAM system with a simple PID controller to control the motion of the PAM. The experiment setup is explained and Ziegler Nichols tuning method is used in getting the approximation PID parameters. The effectiveness of the proposed control algorithm is demonstrated through experiments.